2019
DOI: 10.3390/jcm8122061
|View full text |Cite
|
Sign up to set email alerts
|

We are What We Eat: Impact of Food from Short Supply Chain on Metabolic Syndrome

Abstract: Food supply in the Mediterranean area has been recently modified by big retail distribution; for instance, industrial retail has favored shipments of groceries from regions that are intensive producers of mass food, generating a long supply chain (LSC) of food that opposes short supply chains (SSCs) that promote local food markets. However, the actual functional role of food retail and distribution in the determination of the risk of developing metabolic syndrome (MetS) has not been studied hitherto. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 41 publications
2
54
0
Order By: Relevance
“…Santulli et al provided evidence that the use of the Mediterranean diet based on the short supply chain significantly reduces the incidence of MetS compared to the long supply chain. These authors indicate that the length of the food supply chain is a key determinant of the risk of MetS in the population living on a Mediterranean diet [30]. Furthermore, the study conducted by Assaf-Baut et al among women with and without gestational diabetes mellitus (GDM) in the 12th-14th week after childbirth shows that the intervention on diet reduced the relative risk of MetS, but not the risk of insulin resistance [31].…”
Section: Discussionmentioning
confidence: 97%
“…Santulli et al provided evidence that the use of the Mediterranean diet based on the short supply chain significantly reduces the incidence of MetS compared to the long supply chain. These authors indicate that the length of the food supply chain is a key determinant of the risk of MetS in the population living on a Mediterranean diet [30]. Furthermore, the study conducted by Assaf-Baut et al among women with and without gestational diabetes mellitus (GDM) in the 12th-14th week after childbirth shows that the intervention on diet reduced the relative risk of MetS, but not the risk of insulin resistance [31].…”
Section: Discussionmentioning
confidence: 97%
“…One of the explanations for this trend is departure from the traditional lifestyle and Mediterranean diet, especially in younger people from Mediterranean countries [16,17]. Interestingly, it was found that change in the food supply in the Mediterranean area, especially more readily available mass-produced food from the long supply chain (opposite from the local food markets) was associated with MetS [18]. These trends are very misfortunate and represent a double missed opportunity, because Mediterranean diet was shown to have the capacity for preventing the development of metabolic syndrome, as well as the ability to reverse it in people with or without type 2 diabetes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as aforementioned, we collapsed all groups into one sample and applied multivariate regression analyses to the whole sample in order to account for exercise and diet behavior changes in practice during the intervention period. Third, regarding the dietary intervention, we have to mention that we did not differ short supply chain (SSC) from long supply chain (LSC) food included in the DASH [48]. A recent cross-sectional study found that only individuals adhering to the Mediterranean diet with an SSC had a significantly reduced prevalence of metabolic syndrome compared to those with an LSC [48].…”
Section: Discussionmentioning
confidence: 99%
“…Third, regarding the dietary intervention, we have to mention that we did not differ short supply chain (SSC) from long supply chain (LSC) food included in the DASH [48]. A recent cross-sectional study found that only individuals adhering to the Mediterranean diet with an SSC had a significantly reduced prevalence of metabolic syndrome compared to those with an LSC [48]. Further, recent studies have shown that inflammatory effects of food parameters exist with a high variability [49] due to either a different genetic pattern or to diverse genetic-environmental interactions, and potential interactions (synergism, antagonism) among food parameters.…”
Section: Discussionmentioning
confidence: 99%